1996
DOI: 10.1017/s0048840200024266
|View full text |Cite
|
Sign up to set email alerts
|

ALLA RICERCA DELLA COLLEGIALITÀ Dl GOVERNO: I VERTICI Dl MAGGIORANZA DAL 1970 AL 1994

Abstract: PremessaLe radici della debolezza del governo collegiale nell'Italia repubblicana sono state individuate nel modello costituzionale formale così come fu ideato dai padri fondatori. Ma anche nel fatto che i governi italiani, tranne qualche eccezione, sono sempre stati governi di coalizione, una condizione che necessariamente rende il processo decisionale collegiale molto più complicato e controverso (Pappalardo 1978; Bogdanor 1983; Pridham 1986; Budge e Keman 1990; Laver e Schofield 1990).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Empirical studies (Verzichelli and Cotta 2000) have shown that both the most frequently used arenas, and those employed for the most serious conflicts, were either mixed (involving both government members and actors outside government) or external (many of the meetings being ad hoc and always bringing together the party leaders). A typical arena was the majority summit between prime ministers (except in rare cases) and coalition party leaders and, depending on the case, other actors (Criscitiello 1993(Criscitiello , 1996.…”
Section: The Theoretical Premisementioning
confidence: 99%
“…Empirical studies (Verzichelli and Cotta 2000) have shown that both the most frequently used arenas, and those employed for the most serious conflicts, were either mixed (involving both government members and actors outside government) or external (many of the meetings being ad hoc and always bringing together the party leaders). A typical arena was the majority summit between prime ministers (except in rare cases) and coalition party leaders and, depending on the case, other actors (Criscitiello 1993(Criscitiello , 1996.…”
Section: The Theoretical Premisementioning
confidence: 99%